Reflection and Refraction of the L‐O Mode 5 kHz Saturn Narrowband Emission by the Magnetosheath. Issue 5 (14th March 2022) - Wu, S. Y.; Ye, S. Y.; Fischer, G.; Jackman, C. M.; Wang, J.; Menietti, J. D.; Cecconi, B.; Long, M. Y.
Abstract: The reflection‐by‐sheath mechanism of 5 kHz narrowband emissions (NB) at Saturn is confirmed by Cassini observations during several crossings of the magnetopause, which show that the 5 kHz NB can be prevented from escaping Saturn's magnetosphere. The L‐O mode 5 kHz NB remained visible in areas of low plasma density but disappeared in regions of high plasma density. In three cases, NB disappeared immediately after the crossings of Saturn's magnetopause. A possible reflected NB event observed near the magnetosheath is discussed. This mechanism can help explain the 5 kHz NB observed at low latitudes outside the Enceladus plasma torus and their upper frequency limit variations. This mechanism significantly improves the current understanding of the 5 kHz NB. Plain Language Summary: Very low frequency narrowband radio emissions have been observed at about 5 and 20 kHz by the Voyager and Cassini spacecraft at Saturn. Recently, a statistical survey of Saturn narrowband emissions indicated that the 5 kHz narrowband emissions could be reflected by Saturn's magnetosheath due to the high plasma density within. The work presents evidence to confirm the reflection and refraction of 5 kHz narrowband emissions by Saturn's magnetosheath. The observations of narrowband emissions near Saturn's magnetosheath show that sometimes the 5 kHz narrowband emissions cannot pass the magnetosheath when the plasma density is high enough, at other times the polarization reverses near the magnetosheath, which indicates a reflected signal. This survey confirms the reflection‐by‐sheath mechanism, and it is of special importance because this mechanism significantly improves the current understanding of the Saturn narrowband emissions and explains several features of them. Key Points: The 5‐kHz narrowband emissions (NB) from Saturn can be reflected by density structures in the magnetosheath Reflection leads to depolarization and trapping of NB inside Saturn's magnetosphere The upper frequency limit of trapped NB depends on variations in the magnetosheath and the solar wind